ANALISIS YURIDIS PENYELESAIAN SENGKETA HIBAH DI PENGADILAN TINGGI MEDAN (Studi Kasus Putusan No.142/PDT/2015/PTMDN) - Ria Sintha Devi; Alusianto Hamonangan; Emi Rafika Sitepu (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Darma Agung (LPPM_UDA), 2021)
This gift is regulated in article 1882 of the Civil Code which states, among other things, that the gift must be made with a notary deed, especially for immovable property, while for movable property it can be granted just like that, a gift made outside of it is canceled. Likewise, a grant cannot be renewed, even if it is made with a notary deed, which means that updates on the grant or by making changes or additions from the time the grant was originally made are not allowed. Regarding the reasons for the cancellation of the grant, the cancellation of this grant is regulated by Article 1666 of the Civil Code, which states that a grant cannot be withdrawn or canceled because of it. The problems that will be investigated are: How do you prove the validity of a grant deed in the Case Study of Decision No. 142 / PDT / 2015 / PT.Mdn ?, Why can't a grant be withdrawn but can be canceled? decide the case No. 142 / PDT / 2015 / PT-MDN ?. This study uses a normative legal approach. Normative legal research in this research is carried out on the procedure for settlement of grant disputes through courts. The type of data used in this legal research is secondary data. Secondary data sources in this legal research were obtained from: Primary legal materials, among others: Civil Code, Law No. 48/2009 concerning Judicial Power, Decision No.142 / PDT / 2015 / PTMDN. In proving the validity of a Grant Deed, it must have physical, formal and material evidentiary strength, and the process of making a Grant Deed meets the elements stipulated by Article 1868 of the Civil Code. Basically, a grant is irrevocable but can be canceled based on exceptions that have been determined based on statutory regulations. The Legal Considerations of the Medan High Court Judge against the Simalungun District Court Decision No.55 / Pdt.G / 2014 / PN-Sim regarding the settlement of grant disputes in this case were declared incorrect and wrong because the appellate's memory of appeal is very reasonable based on law and can prove that the object of the dispute is the right of the appellant whose truth cannot be denied by the party being appealed against in the counter memorandum of appeal.